Kebijakan Countercyclical Sebagai Upaya Kesejahteraan Masyarakat - Shara, Made Cinthya Puspita (Jurnal Hukum & Pembangunan, 2022)
The high level of economic growth in Indonesia is in line with the development of businesses that increase capital by making credit agreements with financial institutions. The state of the spread of the co-19 pandemic case has been declared a national disaster, impacting on the implementation of credit agreements between the debtor and financial institutions. Economic problems make it difficult for people to carry out their obligations. Countercyclical buffer policy is a buffer that is carried out by providing additional capital to replace losses if excessive credit growth occurs which has the potential to disrupt financial stability. Bank Indonesia Policy PBI No.17/22/PBI/2015, also the Financial Services Authority Regulation Number 11/POJK.03/2020, and the Financial Services Authority Regulation Number 14/POJK.05/2020 issued with the aim to be able to provide welfare as stated in article 33 of the 1945 Constitution. In this study the authors used a normative research method. Enforcement of these policies becomes an urgency for Indonesia to be able to carry out financial stability by maintaining the level of economic growth of the community and paying attention to the level of welfare.